The risk of high dependency towards middlemen among paddy farmers in Kampung Tedong, Merlimau, Melaka / Nur Juzita Md Fuzi - Md Fuzi, Nur Juzita (Faculty of Plantation and Agrotechnology, 2019)
A middleman is a vital element in every business transaction in the world. The rapid growth of human population has made the farmers need to improve their agricultural production and in the same time protecting their income. Other than being as a service provider to the farmers, middlemen also give risks to farmers in every transaction as they might tend to exploits the farmers with their advantages and knowledge. This study examines the risk of high dependency towards middlemen among paddy farmers in Kampung Tedong, Merlimau, Malacca. A questionnaire and interviews were used to collect the data on the level of dependency towards middlemen. On the basis of data from 59 local farmers in Merlimau, Melaka, the preliminary result shows that several variables such as agricultural input handling, financial status and technology usage have an influence towards high dependency towards middlemen among paddy farmers in the area. The conclusion can also be drawn that despite of the risk that farmers might face while using the middlemen service, the farmers still highly depends on them especially when they are less expose to technology.